Proteomic Characterization of Plasma in Lemierre's Syndrome - Nygren, David; Torisson, Gustav; Happonen, Lotta; Mellhammar, Lisa; Linder, Adam; Elf, Johan; Yan, Hong; Welinder, Charlotte; Holm, Karin (Thrombosis and Haemostasis, 2024)
Background The underlying mechanisms of thrombosis in Lemierre's syndrome and other septic thrombophlebitis are incompletely understood. Therefore, in this case control study we aimed to generate hypotheses on its pathogenesis by studying the plasma proteome in patients with these conditions.Methods All patients with Lemierre's syndrome in the Skåne Region, Sweden, were enrolled prospectively during 2017 to 2021 as cases. Age-matched patients with other severe infections were enrolled as controls. Patient plasma samples were analyzed using label-free data-independent acquisition liquid chromatography tandem mass spectrometry. Differentially expressed proteins in Lemierre's syndrome versus other severe infections were highlighted. Functions of differentially expressed proteins were defined based on a literature search focused on previous associations with thrombosis.Results Eight patients with Lemierre's syndrome and 15 with other severe infections were compared. Here, 20/449 identified proteins were differentially expressed between the groups. Of these, 14/20 had functions previously associated with thrombosis. Twelve of 14 had a suggested prothrombotic effect in Lemierre's syndrome, whereas 2/14 had a suggested antithrombotic effect.Conclusion Proteins involved in several thrombogenic pathways were differentially expressed in Lemierre's syndrome compared to other severe infections. Among identified proteins, several were associated with endothelial damage, platelet activation, and degranulation, and warrant further targeted studies.
Keywords: Lemierre's syndrome; septic thrombophlebitis; Fusobacterium necrophorum; mass spectrometry; thrombogenesis